Experimental Investigation for The Flow Induced Vibration for Pipe Inside Water - Salman, Haitham Mohsin; Mohammed, Ansam Adel (Al-Nahrain Journal for Engineering Sciences, 2020)
Forced vibration has been experimentally investigated on a model consists of circular pipe with1.6m length. The pipe built in tank (1.2m length, 0.6m height and 0.6m width) horizontally at 0.4m height with two different diameters d=15mm and d=35mm. The pipe conveying laminar flow in the fully developed region, of Reynolds number equals 2000. The experimental results of span pipe conveying water at five stations of forced excitation vibration were studied. The harmonic forced vibration with two different excitation frequencies (10 Hz and 15 Hz) are imposed at all of the five locations. The distance between two stations is (0.2m). Two conditions of pipe environment have been applied, the first in air and the other was immersed in water. It is concluded that the effect of flow induced vibration due to the pipe conveying fluid increases the maximum deflection when the fluid speed increases. The water surrounds the pipes reduce the effect of excitation vibration about (33 – 46%). The effect difference between the excitation frequencies was about (4 – 7%).